Pariwisata Semu dan Ketimpangan Nyata: Evaluasi Dampak Sosial-Ekonomi Transformasi Wisata Di Malino, Kabupaten Gowa - thamrin pawalluri (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
The transformation of tourism in Malino since 2015 has shown an increase in the construction of villas, thematic areas, and growth in tourist visits, but has resulted in land conversion, the dominance of external capital, and the marginalization of local communities. This study aims to analyze the socio-economic impacts of changes in tourism spatial planning in Malino, Gowa Regency, using a descriptive qualitative approach based on document studies, field observations, and a review of the latest literature. The results of the study indicate structural inequality in land ownership, changes in the pattern of weak farmers' livelihoods to informal laborers, and the loss of local cultural space in tourism governance. This study confirms that weak spatial planning control and the absence of a community-based tourism model are the main factors of spatial injustice. Research recommendations include the enforcement of regional regulations (RTRW), the formation of local tourism management communities, and the application of the principles of maqashid sharia (hifz al-mal and hifz al-nafs) to create fair, sustainable, and community-oriented tourism development.